DAMPAK PERJANJIAN FOREST LAW ENFORCEMENT GOVERNANCE AND TRADE - VOLUNTARY PARTNERSHIP AGREEMENT TERHADAP EKSPORTIR KAYU INDONESIA KE UNI EROPA - Halifa Haqqi, Amelia Nugroho Ningrum, Setyasih Harini & (Transformasi, 2016)
FLEGT-VPA, created in 2006 and has been through the consideration for 6 years andthen the days of the post of Minister of Forestry Zulkifli Hasan has been approved and signed theagreement with the European Commissioner for Environment Janez Potonik and the Minister ofEnvironment of Lithuania Valentinas Mazuoronis which is Presidency of the EU, at theEuropean Union Headquarters in Brussels, Belgium on 30 September 2013. in an effort toreduce the problem of illegal logging or illegal trade is the case of Indonesia to the EuropeanUnion. This research uses a qualitative research, the object of this research is PT. AnugrahRimba Nusantara in Kalijambe, PT. Roda Jati in Kalioso, teak plantation owners in Gemolong,Indonesian Furniture Association (ASMINDO), and the Ministry of Trade through theDirectorate of Bilateral Cooperation with Sub Europe. Data collection techniques areinterviews, observation, and library research. Data analysis technique used is interactive. Thestudy concluded that with the signing of the agreement between Indonesia FLEGT-VPA with theEuropean Union, slowly Indonesian government can overcome the problems mentioned abovegradually. For wood manufacturers in Sragen recognize more easily the export process usingSVLK. The impact of the timber trade that occurred after the entry into force of SVLK is timberexports to the EU are likely to decline in 2013 since the first year of implementation of SVLK, aswell as the increase in 2014 but did not reach the value of exports in 2010 before using SVLK,which tend to be more export value. Researchers give advice to researchers continued to raisethe topic of the Examining more about the role of VPA in addressing the problem of illegallogging in Indonesia and the Role of the Government of Indonesia in the decision agreeing VPAagreement.Keywords: Forest, Trade, Partnership, Agreement, Policy, Enforcement